If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8=4(2m-2)
We move all terms to the left:
8-(4(2m-2))=0
We calculate terms in parentheses: -(4(2m-2)), so:We get rid of parentheses
4(2m-2)
We multiply parentheses
8m-8
Back to the equation:
-(8m-8)
-8m+8+8=0
We add all the numbers together, and all the variables
-8m+16=0
We move all terms containing m to the left, all other terms to the right
-8m=-16
m=-16/-8
m=+2
| (3x-2)^2=256 | | X/2-1/5=x/3+1/4+1 | | .7526a-3.5512=1.2534a | | k2-7k+20=0 | | -13+19=-7y+5y | | k2-5k+20=0 | | -14.5p=-16.8p-14.26 | | -4(-3x+2)-4x=2(x-1)-2 | | 10x+-6=84 | | -7x+3=-2x+23 | | 3(x−2)+11=−4 | | 7x-3/3x=2 | | 3x-16=2x-25 | | 43000+3200x=57000+2000x | | X^2+16x-88=-8 | | 3x-16=2x-25* | | 19(34-t)+65=118 | | 25-5x=5(5x+3) | | -20+3g=4g | | -17-(-14)=x/11 | | -4x+2(x-5)=-26 | | -4s+8=3s-8-5s | | 0.5÷16+x=16 | | 2x+7=3x–1 | | -12-2m=17m-12 | | 3x/6=4/5+2x+9/2 | | 6/7y=8/21 | | -8x+6(x+4)=6 | | -8g-6=-7g | | 8-7d=1-9d-5 | | 19(40-x)+69=20+55 | | -10+6p=10+4p |